Individuals and Predication - A Neurosemantic Perspective - Klein, Michael; Kamp, Hans (Proceedings of Sinn und Bedeutung, 2019)
In this paper we reflect on the constraints that current knowledge and assumptions in the neurosciences impose on theories of concepts and of linguistic meaning. We focus on the operation of predication. A central contention of this paper is that at the neural level there is no fundamental difference between predicate and predicable - representations of individuals and representations of categories are both feature complexes with basically the same structure. We discuss the structure of such representations and the ways in which they interact in certain simple situations of perception and verbal communication.